Pengaruh aspek psikologis terhadap efektivitas pembelajaran pendidikan agama Islam - Fauzi, Achmad; Karim Amrullah, Abdul Malik; Hanif, Ma’mun (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study focuses on how psychological aspects play a role in determining the effectiveness of Islamic Religious Education (IRE). In the learning process, factors such as motivation, interest, emotions, and personality of students cannot be ignored because they greatly influence how they understand and appreciate religious values. This study uses a qualitative descriptive approach with a literature study method, which is to examine various theories and previous research results relevant to the topic. The data were analyzed through the stages of collection, reduction, and conclusion drawing in a systematic manner. The results showed that when students had strong motivation, stable emotions, and a high interest in religious studies, the learning process became more lively, interactive, and meaningful. Conversely, an unbalanced psychological condition can reduce focus and hinder the understanding of spiritual values. Therefore, PAI teachers need to understand the psychological condition of students in order to create a supportive, warm learning atmosphere that fosters religious enthusiasm in students.